2014
DOI: 10.2214/ajr.13.11819
|View full text |Cite
|
Sign up to set email alerts
|

Pure Ground-Glass Opacity Neoplastic Lung Nodules: Histopathology, Imaging, and Management

Abstract: When pure GGNs are greater than 15 mm in diameter with nodularity or have high pixel attenuation (>-472 HU), the nodules are more likely to be invasive adenocarcinomas. Sublobar resection with a secured safety margin and without nodal dissection is performed for HRCT-suggested pure-GGN invasive adenocarcinomas and has a 100% 5-year survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 58 publications
7
121
2
Order By: Relevance
“…J Thorac Dis 2017;9(12):4967-4978 jtd.amegroups.com and pGGNs with diameter greater than 15 mm are more likely to be IA (11). In our study, the maximum diameter greater than 16.1 mm indicated IA independently, and this was similar with previous study (5)(6)(7)(8)23,24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…J Thorac Dis 2017;9(12):4967-4978 jtd.amegroups.com and pGGNs with diameter greater than 15 mm are more likely to be IA (11). In our study, the maximum diameter greater than 16.1 mm indicated IA independently, and this was similar with previous study (5)(6)(7)(8)23,24).…”
Section: Discussionsupporting
confidence: 90%
“…Because of the limited resolution (0.2-0.3 mm) of CT images, stromal or myofibroblastic invasion of 5 mm or smaller in MIA or even IA greater than 5 mm in size may manifest as pGGN on high resolution CT (5). It has been proved that CT attenuation of IA is higher than its precursors (11), but there is no consensus over the cutoff of CT attenuation to indicate pGGN of IA. One study suggests that pGGNs with mean CT attenuation >−472 Hounsfield unit (HU) are more likely to be IA, with sensitivity of 75% and specificity of 81% (12).…”
Section: Original Articlementioning
confidence: 99%
“…These results indicate that producing VBN to the bronchus that was central or closest to the lesion contributed to successfully reaching the lesion, obtaining EBUS-GS images of the lesion, and increasing diagnostic yield. 15 Lee et al reported that when pure GGO predominant-type lesions are greater than 15 mm in diameter with nodularity or harbor a solid component within them, the lesions are more likely to be invasive adenocarcinoma [28]. Furthermore, in this study, the rate of diagnosed malignancy was high and the diagnostic yield of lesions under 15mm was low (Table3).…”
Section: Commentmentioning
confidence: 60%
“…Several other studies confirmed a well correlation between CT findings and histologic prognostic factors in lung adenocarcinomas (5)(6)(7). However, when pGGOs are greater than 15 mm in diameter or have high pixel attenuation (>−472 HU), the nodules are more likely to be IA (8). Recently, a similar observation has been documented for early stage tumors about GGO component.…”
Section: Introductionmentioning
confidence: 56%
“…In univariate analysis, we found that smaller tumor size and larger GGO proportion were significantly associated with indolent and less aggressive tumors. Similarly, there were several studies also found that the size and mass of the nodule are determinants of invasive adenocarcinoma (8,(16)(17)(18). While, recently an observation found that in patients with tumors smaller than 3 cm, DFS was significantly associated with solid tumor size, but not with whole tumor size in early stage tumors (9).…”
Section: Discussionmentioning
confidence: 84%